Enhancing Mandarin Speaking Skills through Job Interview Simulations for Students in the MBKM MSIB Selection Program - Agwinanda, Almira; Pamuji, Dian Yuni; Marsuki, Ria Riski (Longda Xiaokan: Journal of Mandarin Learning and Teaching, 2025)
This study aims to explore and measure the effectiveness of instructional materials based on job interview simulations in improving students’ Mandarin speaking skills, particularly as a systematic and contextual preparation for the selection process of the Certified Internship and Independent Study Program (MSIB) under the Merdeka Belajar Kampus Merdeka (MBKM) scheme. A mixed-method approach was employed, combining qualitative and quantitative techniques. Qualitative data were collected through classroom observation and students’ verbal responses during simulations, while quantitative data were obtained from pretests and posttests. Initial findings showed that students struggled to comprehend interview questions and provide coherent, appropriate answers. After the simulation sessions, significant improvements were observed in fluency, word choice, intonation, and contextual understanding and response. These results emphasize the urgency of integrating simulation-based learning into Mandarin speaking instruction to prepare students for professional communication in the workplace. This article recommends applying a similar model in other foreign language programs and suggests the development of interactive and adaptive digital instructional resources.